2012
DOI: 10.1002/hed.23170
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of every‐other‐week maintenance cetuximab after first‐line chemotherapy in patients with recurrent or metastatic head and neck squamous cell cancer

Abstract: Every-other-week maintenance cetuximab schedule was well tolerated and did not worsen toxicity that occurred during chemotherapy. In daily practice, this simplified schedule could improve compliance and possibly improve quality of life in patients with recurrent or metastatic HNSCC that showed no progression during first-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…It has been proven previously in colorectal cancer and head and neck cancer patients that weekly cetuximab and biweekly cetuximab is equally effective with respect to target regulation, pharmacokinetics and pharmacodynamic parameters2021. Additionally, it has been shown in prostate cancer patients that docetaxel biweekly is as effective as docetaxel triweekly, but much better tolerated22.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven previously in colorectal cancer and head and neck cancer patients that weekly cetuximab and biweekly cetuximab is equally effective with respect to target regulation, pharmacokinetics and pharmacodynamic parameters2021. Additionally, it has been shown in prostate cancer patients that docetaxel biweekly is as effective as docetaxel triweekly, but much better tolerated22.…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS and OS were 8 and 11 months, respectively, which are also in line with findings for cetuximab plus platinum-based CT in clinical trials (9, 11, 56). Similarly, in a retrospective study of 31 patients with R/M SCCHN, cetuximab plus CT followed by maintenance with biweekly cetuximab led to a stable disease rate of 52%, partial response rate of 39%, and complete response rate of 9% (59). Furthermore, there is evidence that maintenance therapy until PD with cetuximab as a single agent following the EXTREME regimen is also well-tolerated with a good compliance (relative dose intensity = 82%) (53, 59).…”
Section: First-line Treatment Options In R/m Scchnmentioning
confidence: 98%
“…Similarly, in a retrospective study of 31 patients with R/M SCCHN, cetuximab plus CT followed by maintenance with biweekly cetuximab led to a stable disease rate of 52%, partial response rate of 39%, and complete response rate of 9% (59). Furthermore, there is evidence that maintenance therapy until PD with cetuximab as a single agent following the EXTREME regimen is also well-tolerated with a good compliance (relative dose intensity = 82%) (53, 59). Indeed, in the EXTREME trial, the frequency of severe skin reactions in the cetuximab-containing arm decreased from 9 to 5% during the cetuximab maintenance phase (median treatment duration = 29.9 weeks) (60).…”
Section: First-line Treatment Options In R/m Scchnmentioning
confidence: 98%
“…Most common adverse events were grade 3 or 4 febrile neutropenia (5.7%), skin rash (3.8%), or mucositis (3.8%). Bossi et al [36] evaluated cisplatin, 5-FU, and CTX as first-line treatment followed by CTX maintenance every other week. While maintenance patients developed skin rash (grade 3, 16%; grade 2, 23%), fatigue (grade 3, 3%; grade 2, 16%), diarrhea (grade 3, 7%; grade 2, 13%), hypomagnesaemia (grade 4, 3%; grade 3, 3%; grade 2, 19%), and mucositis (grade 3, 3%; grade 2, 23%), the study showed that CTX maintenance was well tolerated.…”
Section: Resultsmentioning
confidence: 99%